2009
DOI: 10.1007/s11814-009-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical variation in bentonite by sulfuric acid activation

Abstract: The physico-chemical behavior of Iranian typical bentonite was characterized during the activation process by sulfuric acid. The main variations were studied by evaluating specific surface area, chemical and mineralogical composition, thermal gravimetric curves, Fourier transform infrared spectrometry pattern, and morphology of starting and activated samples. The effects of acid concentration, particle size distribution, activation temperature and time on specific surface area were discussed. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Similar results were obtained by other workers (Yıldız & Ç alımlı, 2002;Ö nal et al, 2002;Venaruzzo et al, 2002;Rodrigues, 2003;Wu et al, 2006;Vuković et al, 2006;Ö nal & Sarıkaya, 2007;Huaypar et al, 2007;Salem & Karimi, 2009). Turabik & Kumbur (2002) characterized the H 2 SO 4 acid-activation products of bentonite from Ü nye (Turkey) and showed that the intensity of the characteristic peak of montmorillonite for bentonite samples decreased.…”
Section: X-ray Diffractionsupporting
confidence: 82%
“…Similar results were obtained by other workers (Yıldız & Ç alımlı, 2002;Ö nal et al, 2002;Venaruzzo et al, 2002;Rodrigues, 2003;Wu et al, 2006;Vuković et al, 2006;Ö nal & Sarıkaya, 2007;Huaypar et al, 2007;Salem & Karimi, 2009). Turabik & Kumbur (2002) characterized the H 2 SO 4 acid-activation products of bentonite from Ü nye (Turkey) and showed that the intensity of the characteristic peak of montmorillonite for bentonite samples decreased.…”
Section: X-ray Diffractionsupporting
confidence: 82%
“…After acid treatment, a significant difference is not observed between original and activated KT2 and DD3. Under these mild conditions, the FTIR curves showed that a weak destruction of the layers and interlayer space of activated clay was carried [13].…”
Section: Resultsmentioning
confidence: 99%
“…The mycotoxin binder used in this study was a combination of acid-activated bentonite, clinoptilolite, yeast cell walls and organic acids and salt. Acid-activated bentonite increases the adsorption capacity by using a specific acid activation process to increase the surface area and to enlarge pores [ 27 , 28 ]. Clinoptilolite, with a honeycomb like structure, serves to bind a broad range of mycotoxins [ 29 ].…”
Section: Discussionmentioning
confidence: 99%